Structure and function of the topsoil microbiome in Chinese terrestrial ecosystems - Li, Yuqiang; Duan, Yulong; Zhang, Junbiao; Petropoulos, Evangelos; Zhao, Jianhua; Wu, Fasi; Wang, Lilong; Chen, Yun; Wang, Xuyang (Frontiers in Microbiology, 2025)
While soil microorganisms underpin terrestrial ecosystem functioning, how their functional potential adapts across environmental gradients remains poorly understood, particularly for ubiquitous taxa. Employing a comprehensive metagenomic approach across China’s six major terrestrial ecosystems (41 topsoil samples, 0–20 cm depth), we reveal a counterintuitive pattern: oligotrophic environments (deserts, karst) harbor microbiomes with significantly greater metabolic pathway diversity (KEGG) compared to resource-rich ecosystems. We provide a systematic catalog of key functional genes governing biogeochemical cycles in these soils, identifying: 6 core CAZyme genes essential for soil organic carbon (SOC) decomposition and biosynthesis; 62 nitrogen (N)-cycling genes (KOs) across seven critical enzymatic clusters; 15 sulfur (S)-cycling genes (KOs) within three key enzymatic clusters. These functional gene abundances exhibit distinct, geography-driven clustering patterns, strongly correlated with eight environmental drivers (latitude, NDVI, pH, EC, SOC, TN, C:N ratio, and MAP). This work provides a predictive framework and actionable genetic targets (e.g., specific CAZyme, N/S cycling genes) for potentially manipulating soil microbiomes to enhance ecosystem resilience and biogeochemical functions under stress.